Factors Affecting Consumers’ Purchasing of Sachet Skincare Products in Convenience Stores in Bangna District, Bangkok - รัตนพิทักษ์, ทิพมาศ; แก้วพลายงาม, ภัทรารัช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1. study the level of opinions on purchasing skincare products in sachets in convenience stores among consumers in Bangna District, Bangkok 2. To study the purchasing decision of sachet skincare products in convenience stores of consumers in Bangna District, Bangkok 3. To study and compare marketing mix factors with purchasing decision factors of sachet skincare products in convenience stores of consumers in Bangna District, Bangkok. The sample group consisted of 400 consumers who purchased sachet skincare products at convenience stores in Bangna District, Bangkok. Convenience Sampling method was used, the survey and data collection tool was a questionnaire, The statistics used in the analysis were frequency, percentage, mean, and standard deviation, and compare using multiple regression analysis statistics using the Enter method.          The research results found that the demographic factors affecting the purchasing of sachet skincare products in convenience stores of consumers in Bangna District, Bangkok, the majority of the respondents were female, aged 21-30 years, had a bachelor's degree, worked as employees in private companies and had a monthly income of 12,000-20,000baht, Behavioral factors affecting consumers' purchasing of sachet skincare products in convenience stores in Bangna District, Bangkok. Most respondents' favorite convenience store is 7-Eleven, the frequency of purchasing skincare products is 1-2 times per week, the reason for purchasing skincare products is the low price. The person or media that influences the purchasing decision is myself. Marketing mix factors affecting consumers' purchasing decisions for sachet skincare products in convenience stores in Bangna District, Bangkok. Overall, the respondents' opinions were at the highest level. When considering each aspect, there were opinions at the highest level in 4 areas as follows: product, promotion, price, and distribution channels. There were opinions at the highest level in 3 areas as follows: physical characteristics, process, and personnel, respectively. Factors in deciding to purchase skincare products in sachet form at convenience stores of consumers in Bangna District, Bangkok. Overall, the opinions of the respondents were at the highest level. When considering each aspect, there were opinions at the highest level in 3 aspects as follows: problem awareness, information seeking, and opinions at the highest level in 2 aspects as follows: post-purchase behavior, purchase decision, and alternative evaluation, respectively. A comparison of marketing mix factors affecting consumers' purchasing decision in sachet skincare products in convenience stores in Bangna District, Bangkok. It was found that marketing mix factors, product aspects, and marketing promotion aspects had a statistically significant effect on consumers' purchasing decisions for sachet skincare products in convenience stores in Bangna District, Bangkok at a level of .01., It shows that each decision to purchase a sachet of skincare products will have different needs and steps entrepreneurs should clearly present the benefits of sachet skincare products, their ability to correct facial and skin imperfections, and the benefits gained from using the products product quality and safety standards are tested by certified agencies in both the short and long term to build consumer confidence, increase the chances of repeat purchases, and help expand the customer base through word-of-mouth.